On an energy exchange process and appearance of chaos in a non-ideal portal frame dynamical system - Felix, Jorge Luis Palacios; Balthazar, José Manoel [UNESP]; Brasil, Reyolando Manoel Lopes Rebello da Fonseca; Paula, Aline Souza de (Springer Nature, 2013)
In this paper, we consider non-ideal excitation devices such as DC motors with restrictenergy output capacity. When such motors are attached to structures which needexcitation power levels similar to the source power capacity, jump phenomena and theincrease in power required near resonance characterize the Sommerfeld Effect, actingas a sort of an energy sink. One of the problems often faced by designers of suchstructures is how to drive the system through resonance and avoid this energy sink.Our basic structural model is a simple portal frame driven by a num-ideal powersource-(NIPF). We also investigate the absorption of resonant vibrations (nonlinearand chaotic) by means of a nonlinear sub-structure known as a Nonlinear Energy Sink(NES). An energy exchange process between the NIPF and NES in the passagethrough resonance is investigated, as well the suppression of chaos.
Keywords: Non-ideal structure; Nonlinear energy sink; Chaos